Expressive Illocutionary Acts found in Spider-Man: Across the Spider-Verse Movie - I Putu Yudi Pranata; I Gusti Ayu Vina Widiadnya Putri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study examine expressive illocutionary actions Spider-Man: Across The Spider-Verse are main subject of this study. Aim of this research is to categorise the forms of expressive illocutionaries. actions in the speech and the situation's context in the Spider-Man: Across the Spider-Verse movie. The researcher used Halliday and Hassan's (1985) situational context and Searle's (1979) categorization theory of illocutionary actions in this investigation. This research uses a descriptive-qualitative technique to analyse the data. given that the findings may take the form of words or phrases. Using the data source from this study, the researcher successfully classified five distinct expressive illocutionary acts. According to this study's findings, every character in the movie made 25 utterances that demonstrated expressive speech actions. We categorize ten statements as indicative of gratitude, five as evocative of compliments, four as apologetic, two as expressive of complaint, and four as expressive of protest. This movie's expression of gratitude is the most prominent.